Social responsibility of public accountant in carrying out his work in mining activity - Acevedo-Pérez, Ana Rocío; Acevedo-Pérez, María Claudia; Rodríguez, Luis Alberto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
The accounting professional in recent times, as a major player, has been questioned in the performance of his work and even frequently involved with corporate financial scandals, putting into question the social responsibility of his profession. However, here, the analysis of the accounting profession is directed specifically to watch the behavior of the accountant in a particular sector such as mining, mainly in relation to the advise in the exploitation of coal. This paper presents the results of the investigation on public accountants who provide advisory services to entrepreneurs in the mining sector. It inquires also on issues related to the level and quality of the advice that they provide in different topics such as economic, administrative , tax, labor , social and environmental issues in relation to the development of the activity.  Similarly the accountant has an ethical commitment to both organizations and the different groups that are linked directly or indirectly to maintain balance in organizations through the provision of information to related parties on their rights that correspond to them in the development of the activity, and as an administrator and manager of information in decision-making contributes to the generation of the common welfare.  Finally, the social responsibility of the public accountant goes beyond the commitment to the State and the organizations in which they work, because there is a commitment to other stakeholders including the environment and society.